An English Country House in Calcutta: mapping networks between Government House, the statesman John Adam, and the architect Robert Adam - Sydney Ayers (ABE Journal)
Government House in Calcutta, today known as the Raj Bhavan of West Bengal, was built between 1799 and 1803 as the official residence for the Governor-General of Fort William, then the 1st Marquess Wellesley. It is well-established that Government House is modelled after Kedleston Hall in Derbyshire, England, known for the involvement of Robert Adam in its design. A significant fact linking Adam, and therefore Kedleston, with Government House is the previously unacknowledged presence of Adam’s great-nephew, the statesman John Adam, in Calcutta at the time Government House was designed and built. In the exploration of Scottish architectural and familial networks within the British empire, this article seeks to locate the identities of Robert Adam and John Adam within a series of exchanges: between Government House and Kedleston Hall; between public buildings and private houses; between India and Britain; and finally between Scottish, English and British identities. In the context of these exchanges, the study of Government House allows us to connect Robert Adam and John Adam, explore concealments of Scottish identity, and ultimately map previously unknown familial, professional and architectural networks.